The Measurement of Firm Size: Theory and Evidence for the United States and the United Kingdom - Smyth, David J.; Boyes, William J.; Peseau, Dennis E. (The Review of Economics and Statistics, 1975)
David J. Smyth, William J. Boyes, Dennis E. Peseau, The Measurement of Firm Size: Theory and Evidence for the United States and the United Kingdom, The Review of Economics and Statistics, Vol. 57, No. 1 (Feb., 1975), pp. 111-114